Dilālah Maqomlafaz Tasbih in the Perspective of the Quran - Abdul Halim (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
The word tasbih, as an expression of praise for the greatness of Allah, has an important position in the teachings of the Koran. Although tasbih is generally understood as a form of exaltation, in the Al-Quran, tasbih contains various maqom that reflect spiritual dimensions and deeper understanding. This research aims to examine the maqom of lafaz tasbih in the perspective of the Koran, with a focus on the four main maqom: Maqom tanzih (gift of purity), maqom at-Thalab (supplication), maqom nafi (disclaimer), and maqom al-Ta'ajjub (surprise). The method used is qualitative with a descriptive-analytic approach to understand the context and purpose of using tasbih lafaz in the verses of the Koran. The results of the research show that the pronunciation of tasbih has varied functions according to the context, including as a form of glorification of Allah's holiness (maqom Tanzih), a request for His mercy (maqom at-Thalab), an affirmation of the denial of bad qualities for Allah (maqom Nafi), and an expression of surprise at His power (maqom al-Ta'ajjub). In conclusion, understanding the maqom maqom of tasbih provides depth in the practice of worship and appreciation of the nature of God's greatness which is reflected in every word of the tasbih.